2021
DOI: 10.1186/s12885-021-08388-1
|View full text |Cite
|
Sign up to set email alerts
|

Pooled CRISPR screening in pancreatic cancer cells implicates co-repressor complexes as a cause of multiple drug resistance via regulation of epithelial-to-mesenchymal transition

Abstract: Background Pancreatic ductal adenocarcinoma (PDAC) patients suffer poor outcomes, including a five-year survival of below 10%. Poor outcomes result in part from therapeutic resistance that limits the impact of cytotoxic first-line therapy. Novel therapeutic approaches are needed, but currently no targeted therapies exist to treat PDAC. Methods To assess cellular resistance mechanisms common to four cytotoxic chemotherapies (gemcitabine, 5-fluoroura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 62 publications
1
17
0
Order By: Relevance
“…Increased expression of CD44 , a cell surface protein important for cell adhesion and migration, is associated with a more mesenchymal-like phenotype which is characteristic of EMT 20 . Here we have shown that the mesenchymal marker, CD44 transcript and protein are more abundant in cells with HDAC1 overexpression, agreeing with our past work showing that HDAC1 overexpression leads to increased migration 9 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Increased expression of CD44 , a cell surface protein important for cell adhesion and migration, is associated with a more mesenchymal-like phenotype which is characteristic of EMT 20 . Here we have shown that the mesenchymal marker, CD44 transcript and protein are more abundant in cells with HDAC1 overexpression, agreeing with our past work showing that HDAC1 overexpression leads to increased migration 9 .…”
Section: Discussionsupporting
confidence: 93%
“…HDAC1 expression has been previously linked to increased cellular resistance to cytotoxic chemotherapeutic drugs 9 . To further evaluate the effects of HDAC1 overexpression on chemotherapeutic resistance, we used CRISPRa 17 to generate a stable MIA PaCa-2 cell line (MP2_HDAC1_OE) expressing HDAC1 at ~3 times the levels of the levels of the control line (MP2_NTC) which expresses a non-targeting control guide ( Supplementary Data Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these genes, HDAC1 overexpression caused an enrichment of certain genes implicated in EMT. Intriguingly, the expression of canonical EMT transcriptional regulators SNAI1, SNAI2 or TWIST1 was not altered, pointing to the involvement of a partial EMT in this phenomenon [ 46 ].…”
Section: Crispr-based Forward Genetic Screens and Emtmentioning
confidence: 99%
“…Using PDAC cell lines and combining the previously mentioned assays with CRISPR-Cas9 technique has revolutionized the field of metastasis research. Currently, there are available genome-wide or custom made sgRNA CRISPR libraries that have helped identify genes promoting migration, chemoresistance or radioresistance such as Histone Deacetylase 1, ATP binding cassette subfamily G member 2, Endoplasmic reticulum-associated protein degradation ( Du et al, 2021 ; Ramaker et al, 2021 ).…”
Section: In Vitro Preclinical Modelsmentioning
confidence: 99%